Testimony about my Bishop - Kubiś, Adam (Analecta Cracoviensia, 2013)
The paper is a small part of the books of Rev. Adam Kubiś on card. Franciszek Macharski. The article presents an abbreviated biography of the Cardinal starting with his priesthood and concluding with his becoming a cardinal. The text offers some personal reflections on the person, life and work of card. Franciszek Macharski from the perspective of Rev. Adam Kubiś who worked very closely with the Cardinal for many years.